MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SLB NEGERI SRI MUJINAB PEKANBARU - Hartini Hartini; Hendri Marhadi; M. Nur Mustafa (STKIP Pesisir Selatan, 2026)
Educational infrastructure is the factor that contributes to the success of a learning process at school. The principal has important role in the infrastructure management to improve the learning quality at school. This study used qualitative data collection techniques such as observation, interview, document study. The analytic method was carried out by data collection, data reduction, data presentation and drawing conclusions. The result shows that infrastructure management at SLB Negeri Sri Mujinab is implemented based on infrastructure regulation set by the government. The infrastructure management includes planning, procurement, maintenance, inventory control and disposal. Planning is conducted at the beginning of year, involving the principal, vice principal, teachers, and staffs. Procurement is realized using BOS funds, and administrative staffs conduct an inventory. Maintenance and repairs are done to maintain facilities. Report was submitted to the education office. Limited human resources and inadequate infrastructure are not the main obstacles to improving the quality of learning. Cross-functional involvement between teachers and educational staff in managing facilities and infrastructure can create efficiencies in internal management and maintain the quality of learning. The lack of facilities and infrastructure actually encourages teachers to be more creative in modifying and maximizing adaptive learning media for children with special needs.